Avoidance of Maternal Cell Contamination and Overgrowth in Isolating Fetal Chorionic Villi Mesenchymal Stem Cells from Human Term Placenta. (16th February 2017) - Sardesai, Varda S.; Shafiee, Abbas; Fisk, Nicholas M.; Pelekanos, Rebecca A.
Abstract: Human placenta is rich in mesenchymal stem/stromal cells (MSC), with their origin widely presumed fetal. Cultured placental MSCs are confounded by a high frequency of maternal cell contamination. Our recent systematic review concluded that only a small minority of placental MSC publications report fetal/maternal origin, and failed to discern a specific methodology for isolation of fetal MSC from term villi. We determined isolation conditions to yield fetal and separately maternal MSC during ex vivo expansion from human term placenta. MSCs were isolated via a range of methods in combination; selection from various chorionic regions, different commercial media, mononuclear cell digest and/or explant culture. Fetal and maternal cell identities were quantitated in gender-discordant pregnancies by XY chromosome fluorescence in situ hybridization. We first demonstrated reproducible maternal cell contamination in MSC cultures from all chorionic anatomical locations tested. Cultures in standard media rapidly became composed entirely of maternal cells despite isolation from fetal villi. To isolate pure fetal cells, we validated a novel isolation procedure comprising focal dissection from the cotyledonary core, collagenase/dispase digestion and explant culture in endothelial growth media that selected, and provided a proliferative environment, for fetal MSC. Comparison of MSC populations within the same placenta confirmed fetal to be smaller, more osteogenic and proliferative than maternal MSC. We conclude that in standard media, fetal chorionic villi-derived MSC (CV-MSC) do not grow readily, whereas maternal MSC proliferate to result in maternal overgrowth during culture. Instead, fetal CV-MSCs require isolation under specific conditions, which has implications for clinical trials using placental MSC.